2020
DOI: 10.1073/pnas.1910704117
|View full text |Cite
|
Sign up to set email alerts
|

What music makes us feel: At least 13 dimensions organize subjective experiences associated with music across different cultures

Abstract: What is the nature of the feelings evoked by music? We investigated how people represent the subjective experiences associated with Western and Chinese music and the form in which these representational processes are preserved across different cultural groups. US (n = 1,591) and Chinese (n = 1,258) participants listened to 2,168 music samples and reported on the specific feelings (e.g., “angry,” “dreamy”) or broad affective features (e.g., valence, arousal) that they made individuals feel. Using large-scale st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
116
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 53 publications
(132 reference statements)
7
116
0
2
Order By: Relevance
“…Second, as the present study is designed to test existing theoretical frameworks of emotion in the context of fMRI research, our data are not suited to discover new dimensions of affective quality. Some new studies find additional dimensions (e.g., Cowen, Fang, Sauter, & Keltner, 2020), and other new studies continue to confirm valence and arousal as principle dimensions (Jackson, Watts, Henry, List, Forkel, Mucha et al, 2019). Future studies involving a vast dataset that surveys affective quality from a broad range of stimuli may be able to utilize a data-driven approach to meet such goals.…”
Section: Limitationsmentioning
confidence: 92%
“…Second, as the present study is designed to test existing theoretical frameworks of emotion in the context of fMRI research, our data are not suited to discover new dimensions of affective quality. Some new studies find additional dimensions (e.g., Cowen, Fang, Sauter, & Keltner, 2020), and other new studies continue to confirm valence and arousal as principle dimensions (Jackson, Watts, Henry, List, Forkel, Mucha et al, 2019). Future studies involving a vast dataset that surveys affective quality from a broad range of stimuli may be able to utilize a data-driven approach to meet such goals.…”
Section: Limitationsmentioning
confidence: 92%
“…Unlike speech or noise, music has a remarkable function of evoking and affecting listeners’ emotions 19 , 20 . Background music provides a unique window into how the brain works when music and cognitive tasks are presented simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the structure of diverse emotional experiences, Cowen and Keltner (2017, 38 Furthermore, they found that the affective dimensions explained only a fraction of the 48 4 variance in self-reports of subjective experience when compared to emotion categories, 49 a finding that has now been replicated in studies of facial expression, speech prosody, 50 nonverbal vocalization, and music (Cowen and Keltner, 2019;Cowen et al, , 51 2019aCowen et al, , 2020. This work lays a foundation for examining the neural bases of emotional 52 experience in terms of a rich variety of states, as well as whether -at the level of 53 neural response -categories or dimensions organize the experience of emotion, and 54 how a diverse array of states cluster in their neural representations.…”
Section: Introduction 18mentioning
confidence: 99%